Temperature and cosolvent composition effects in the solubility of methylparaben in acetonitrile + water mixtures (2019)
The solubility of methylparaben was determined in acetonitrile + water mixtures at several temperatures (278.15 K to 318.15 K). The solubility curves as a function of acetonitrile ratio showed a maximum at a mass fraction of acetonitrile 0.85 at all te